Does the timing of work integrated learning affect graduate employability outcomes? - Garwe, E.C. (South African Journal of Higher Education, 2020)
Employability is a critical quality measure of student lifelong success that goes beyond grade achievement and often guides students’ choice of university and profession. Whilst studies highlighting the importance of work-integrated learning (WIL) in improving employability abound, there is a dearth of knowledge on the efficacy of timing of WIL as a variable in improving employability. The longitudinal study, carried out in a 3-year annual questionnaire-based survey, examines the effect of timing of WIL on employability status when student performance is held constant. Graduates possessing the same performance level (academic degree class 2.1) showed different levels of economic-engagement achievements depending on whether they engaged in WIL prior to their studies (Group A), throughout the learning period (Group B) or for nine months during the third year (Group C) of their studies. Although the findings revealed differences between timing of WIL and the nature of work engagement, all the graduates endorsed the critical role of WIL in building work-related competencies and thus improving employability. The findings are useful in promoting the necessary diversity in WIL curriculum design to facilitate quality and inclusive higher education.